On the Characterization of the SDET Role in Agile Projects: Expected Skills, Responsibilities, and Practices - Toscani, Carolina; Couto, Júlia; Kroll, Josiane; Dutra, Alessandra; Marczak, Sabrina; Priklandnick, Rafael (Anais da Escola Regional de Engenharia de Software (ERES); 2017: Anais da I Escola Regional de Engenharia de Software, 2017)
Software Development Engineer in Test (SDET) is a formal title for a software tester in software development context. In this paper, we report on a systematic literature review on the SDET role in agile projects. From the 27 se- lected papers, we extracted SDET role’ skills, practices and responsibilities. For instance, we found that motivation, flexibility, and work experience in software engineering are important skills for the SDET be able to perform her work. We also found that developing the system, performing automated unit test, and per- forming exploratory tests are among the main responsibilities of a SDET. Test automation, A/B test, and Behavior-Driven Design are some of the most cited practices of this role in agile projects.